2019
DOI: 10.1002/jsfa.9553
|View full text |Cite
|
Sign up to set email alerts
|

Separation, biochemical characterization and salt‐tolerant mechanisms of alkaline protease from Aspergillus oryzae

Abstract: BACKGROUND The salt tolerance of proteases secreted by Aspergillus oryzae 3.042 closely relates to the utilization of raw materials and the quality of soy sauce. However, little is known about the salt‐tolerant proteases and their salt‐tolerant mechanisms. RESULTS In this study, we isolated and identified a salt‐tolerant alkaline protease (AP, approximately 29 kDa) produced by A. oryzae 3.042. It was considered as a metal‐ion‐independent serine protease. The optimum and stable pH values were both pH 9.0 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Soy sauce is one of the most widely accepted traditional fermented soybean products owing to its unique taste, aroma and nutritional content. It is mainly produced from the whole soybeans or the defatted soybeans via fermentation using Aspergillus oryzae 1 . Soy sauce fermented from different raw materials (whole soybeans or defatted soybeans) can cause differences in taste, odor, color, nutrition and price.…”
Section: Introductionmentioning
confidence: 99%
“…Soy sauce is one of the most widely accepted traditional fermented soybean products owing to its unique taste, aroma and nutritional content. It is mainly produced from the whole soybeans or the defatted soybeans via fermentation using Aspergillus oryzae 1 . Soy sauce fermented from different raw materials (whole soybeans or defatted soybeans) can cause differences in taste, odor, color, nutrition and price.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of essential water was a possible cause of enzyme deactivation due to the collapse of the ordered secondary structure. The high proportion of ordered secondary structures of AOIM was benefit to keep good stability in high salinity (Gao et al, 2019), the same as in this trace water-in-oil system.…”
Section: Effect Of the Trace Water-in-oil Medium On The Conformation Of Four Lipasesmentioning
confidence: 75%
“…The AOIM model protease (PDB accession no. 4K90.pdb, 81% similarity) indicated the highest similarities to non-salt-tolerant neutral protease, which was isolated from A. oryzae 3.042 (Gao et al 2019). The lipase crystal structures with original crystal water (treated as the trace water) were added in a box with a size of 7.292 × 7.615 × 7.533 nm using a minimum distance of 12 Å between the box boundary and the protein.…”
Section: Molecular Dynamics Simulation For the Catalyzed Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halotolerant enzymes are commonly produced by halotolerant microorganisms (Graziano and Merlino, 2014). For example, Gao et al (2019) reported that the proteases secreted by Aspergillus oryzae was more stable than non-salttolerant proteases at high salinity, remaining 20% active even in the presence of 3.0 mol L −1 NaCl after 7 days (Gao et al, 2019). An protease was also isolated from the halotolerant organism Lycinibacillus macrolides, with activity of 304 U mL −1 in highly saline conditions (>4%) (Pounsamy et al, 2017).…”
Section: Bioaugmentation Using Enzymes As Biodegrading Agentsmentioning
confidence: 99%